New species of the Hypoxys triangularis group and the first contribution on the morphology of the internal genitalia of Hypoxys Amyot & Serville, 1843 (Hemiptera: Pentatomidae: Edessinae) - de Paiva Cunha, Eduardo Victor; Fernandes, José Antônio Marin (Zootaxa, 2022)
Hypoxys is the second most diverse genus of Edessinae, but it still has many new species to be described. The taxon was divided into four species groups, among these the H. triangularis group currently has the fewest number of species. This group is formed by H. triangularis (Dallas, 1851), H. capito (Breddin, 1904) and H. subrastratus (Bergroth, 1891). In this study, we describe five new species: H. myrtacivorus sp. n.; H. striatus sp. n.; H. saltensis sp. n.; H. curvatus sp. n. and H. ocanensis sp. n. Additional diagnostic characteristics were added to the H. triangularis group and described species. Internal genitalia of both sexes of Hypoxys species are presented for the first time. Diagnoses for the new species, distributional map and identification key are provided.